2020
DOI: 10.1177/1945892420912152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chronic Sinonasal Disease Symptoms in an Urban Homeless Population

Abstract: Background The urban homeless population has increased exposure to risk factors associated with chronic rhinosinusitis (CRS). However, a gap in knowledge of the prevalence of sinonasal symptoms in these demographic limits complete understanding of CRS epidemiology. There is a need to elucidate sinonasal disease burden in this vulnerable patient population to bring awareness to any existing disparities. Objective To assess the prevalence, severity, and associated factors of CRS clinical symptoms and health-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…6 Of those individuals with potential CRS, only 18% had ever been seen by a physician for their symptoms. 6 Studies of healthcare disparities in CRS have also demonstrated an association between non-white race and more severe CRS symptoms. Konsur et al published a large prospective cohort study assessing differential CRS outcomes based on race.…”
Section: Crs Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…6 Of those individuals with potential CRS, only 18% had ever been seen by a physician for their symptoms. 6 Studies of healthcare disparities in CRS have also demonstrated an association between non-white race and more severe CRS symptoms. Konsur et al published a large prospective cohort study assessing differential CRS outcomes based on race.…”
Section: Crs Severitymentioning
confidence: 99%
“…6 Of those individuals with potential CRS, only 18% had ever been seen by a physician for their symptoms. 6…”
Section: Healthcare Disparities In Crsmentioning
confidence: 99%
“…A few studies have focused on otolaryngology diseases in the homeless population 8–13 . Gurgel et al 12 evaluated otolaryngology needs in 11,690 homeless patients and found a prevalence of 15.2%; the most common diagnoses were upper respiratory infections, cough, dysphagia, and disorders of the ear.…”
mentioning
confidence: 99%
“…6,7 A few studies have focused on otolaryngology diseases in the homeless population. [8][9][10][11][12][13] Gurgel et al 12 evaluated otolaryngology needs in 11,690 homeless patients and found a prevalence of 15.2%; the most common diagnoses were upper respiratory infections, cough, dysphagia, and disorders of the ear. Wu et al 8 examined 100 adult homeless individuals in Toronto, Canada, and identified 22 patients with otolaryngology needs, including 2 head and neck masses.…”
mentioning
confidence: 99%
“…This current issue also contains several very unique articles which explore correlations in trends of sinusitisrelated online searches, 4 characterization of CRS in an urban homeless population, 6 an analysis of Eustachian tube dysfunction symptoms in CRS patients, 10 and a pilot study of a prospective needs assessment of mental health treatment options in patients with CRS. 11 Hahn et al 13 report their promising results on the clinical impact of maintenance therapy with daily acetylsalicylic acid on symptom control in patients with CRS with polyps (13).…”
mentioning
confidence: 99%